Post-translocation spatial ecology and survival of muskrats (Ondatra zibethicus) in lacustrine wetlands. - Matykiewicz, Benjamin Robert (Kansas State University, 2020)
Translocation is a common wildlife management tool though managers often lack follow-up information regarding overall effectiveness of these efforts. Muskrats (Ondatra zibethicus) are native semi-aquatic herbivores with a rich cultural and economic history in North America. Muskrats have been positively associated with increased species richness within wetlands and can act as drivers of disturbance through intense herbivory at high population densities. Currently, muskrats are experiencing long-term and widespread population declines across their native range. Translocations may hold potential for muskrats to restore local populations and mitigate declines. However, it is unclear how translocating muskrats will affect their survival, post-translocation movements, and space use – all critical to effective translocation efforts. I live-trapped muskrats (n = 65) during the summers of 2018-2019 in Voyageurs National Park, MN, USA and assessed the effects of translocation on weekly survival rates and space use patterns. I implanted muskrats with internal VHF transmitters, moved them to treatment wetlands, and tracked space use, survival, and cause-specific mortality. On average, individuals traveled 2.2 km (0.12-10.11 km) from release sites and established a home range within 8 days post-translocation. There was no evidence of homing behavior (i.e., returning to their previous home range). Weekly survival rate was low (0.95, SE = 0.001) and my top known-fate survival model indicated that beaver lodge use and year of release (likely a function of the difference in release techniques between years) had the most influence on post-translocated muskrats. My study provides the first empirical assessment of translocation effects on muskrats and establishes a methodological technique to assess future efforts to use muskrats as a native biocontrol of T. x glauca.
Keywords: Muskrat; Translocation; Survival; Dispersal; Beaver